2003
DOI: 10.1016/j.hep.2003.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Humoral and cardiac effects of TIPS in cirrhotic patients with different "effective" blood volume

Abstract: The aim of this study was to evaluate the cardiac effects of transjugular intrahepatic portosystemic shunts (TIPS) in cirrhotic patients with different effective blood volume. Twodimensional echocardiography was performed before and 7 and 28 days after TIPS insertion in 7 cirrhotic patients with PRA <4 ng/mL/h (group A, normal effective blood volume) and 15 with PRA >4 ng/mL/h (group B, reduced effective blood volume). Before TIPS, most cirrhotic patients showed diastolic dysfunction as indicated by reduced ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 49 publications
0
20
0
1
Order By: Relevance
“…Patients with advanced cirrhosis and portal hypertension can develop cardiomyopathy with left ventricular diastolic dysfunction [21] , hyperdynamic state, volume overload, and less commonly portopulmonary hypertension; these conditions can be aggravated with the insertion of TIPS [14,17,[22][23][24] . The placement of TIPS rapidly increases the RV preload and afterload, which can lead to overt heart failure, pulmonary hypertension and death [11,14,16,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] . RA pressure obtained before TIPS could be of value in clinical practice; physicians may elect to abort a TIPS procedure based on this hemodynamic parameter.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with advanced cirrhosis and portal hypertension can develop cardiomyopathy with left ventricular diastolic dysfunction [21] , hyperdynamic state, volume overload, and less commonly portopulmonary hypertension; these conditions can be aggravated with the insertion of TIPS [14,17,[22][23][24] . The placement of TIPS rapidly increases the RV preload and afterload, which can lead to overt heart failure, pulmonary hypertension and death [11,14,16,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] . RA pressure obtained before TIPS could be of value in clinical practice; physicians may elect to abort a TIPS procedure based on this hemodynamic parameter.…”
Section: Discussionmentioning
confidence: 99%
“…In our population, there was a trend towards more astma/COPD cases among participants with an E/A ratio of under 0.75. Liver failure is also known to cause intravascular hypovolaemia, and an inverted mitral inflow pattern has been shown to co-exist with liver cirrhosis [11,12]. Unfortunately, liver function was not measured in the present data.…”
Section: Discussionmentioning
confidence: 71%
“…Among populations of advanced age, the attenuation of the E/A ratio can be caused by many mechanisms not related to heart failure [11][12][13][14]. Elderly have often impaired ability to sense thirst [23], and chronic dehydration is common among the elderly, especially among cognitively impaired individuals [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 However, E/A ratio have several limitations as it is strongly dependent on preload and often requires age correction. 39 A recent study by Ruiz del Arbol et al showed LVDD in 37/80 (46.2%) with Tissue Doppler Imaging (TDI) in cirrhotic patients. They also found LVDD occurs simultaneously with other changes in cardiac structure and function and is associated with an impairment of effective arterial blood volume.…”
Section: Discussionmentioning
confidence: 98%